Reliability of black hole mass estimation from broad emission lines in spectra of the type 1 active galactic nuclei - Marčeta-Mandić Slađana (Serbian Astronomical Journal)
This study investigates reliability of the black hole mass (MBH) estimation using broad emission lines in spectra of the Type 1 Active Galactic Nuclei (AGN) from the Sloan Digital Sky Survey (SDSS). Masses derived from the broad Hα and Hβ emission lines are compared with the stellar velocity dispersion (σ*). The results show that the MBH-σ* correlation strengthens in spectral sub-samples characterized by broader Hβ, red asymmetry in Hβ profiles, high continuum luminosity, and absence of outflows. These findings suggest that Hα and Hβ provide more accurate black hole mass estimates for objects with such spectral properties.